Indigenous Community: A Phenomenological Study of Psychological Well-being Among Serat Menyuri Practitioners in the Kalitanjung Community - Amien Wahyudi; Agus Supriyanto; Hardi Prasetiawan; Shopyan Jepri Kurniawan (Al Musyrif: Jurnal Bimbingan dan Konseling Islam, 2026)
This study examines the psychological well-being of the Kalitanjung indigenous community, a Kejawen (Javanese spirituality) group that adheres to the Serat Menyuri teachings. Qualitative phenomenological approach involving three respondents who are practitioners of the Serat Menyuri teachings. Data were collected through focus group discussions, supplemented by literature reviews and documentation. Data analysis was conducted using thematic methods, supported by Quirkos software. The results show that the psychological well-being of this community isn't rooted in individuality, but rather in a deep sense of connectedness and communal awareness as the foundation for the emergence of psychological well-being. Aspects of psychological well-being are manifested through strong social cohesion so that autonomy is understood as the ability to build social networks, and environmental mastery is reflected in the structured distribution of roles. Interpersonal relationships are built on trust and openness, while environmental mastery is associated with a shared mindset to seek peace in old age. Life goals and personal growth are collective, focused on preserving traditions and emotional support among members. Novelty from this study about social cohesion, structured roles, and collective goals forms the main foundations that enable this community to remain resilient, both psychologically and as the foundation of Islamic counseling.